Economic Ability as a Kafā'ah Principle and the Recognition of Difabel Marriage Guardian in As-Silāḥ fī Bayāni An-Nikāḥ by Khalil Al-Bangkalany - Zuhriyah, Lailatul; Muna, Nailal (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Fuqaha (Islamic jurists) have extensively deliberated upon the notions of kafā'ah and marriage guardianship. Many subsequent scholars have adopted and adapted the opinions of their predecessors concerning these two concepts. This article examines Al-Bangkalany's perspectives on kafā'ah and marriage guardianship as presented in his book As-Silāḥ fī Bayāni An-Nikāḥ. Within this work, Al-Bangkalany's viewpoint on kafā'ah and marriage guardianship is considered distinct. The contents of this article are the outcome of a comprehensive literature review, involving the analysis of the concepts of kafā'ah and marriage guardianship within the book As-Silāḥ fī Bayāni An-Nikāḥ. According to Al-Bangkalany, the notion of kafā'ah, as portrayed in fiqh literature, does not serve as the primary criterion for selecting a bride. Instead, the pivotal principle revolves around the groom's ability to adequately provide for the family's needs. Furthermore, Al-Bangkalany argues that individuals with disabilities, such as blindness, deafness, or muteness, can assume the role of marriage guardians after receiving suitable assistance. The intellectual capacity of the guardian, on the other hand, does not determine their eligibility for the role of marriage guardian.[Para fuqaha telah mendiskusikan konsep kafā'ah dan wali nikah. Pendapat-pendapat fuqaha tersebut biasanya diapropriasi oleh ulama-ulama belakangan baik dengan atau tanpa memodernisasi konsep tersebut. Artikel ini mengkaji pendapat Al-Bangkalany tentang kafā'ah dan wali perkawinan dalam kitabnya As-Silāḥ fī Bayāni An-Nikāḥ. Dalam buku tersebut, ia dianggap memiliki pandangan tentang Kafā'ah dan wali nikah yang unik. Artikel ini merupakan penelitian pustaka. Data dikumpulkan dengan menelaah konsep kafā'ah dan wali nikah dalam buku Al-Bangkalany As-Silāḥ fī Bayāni An-Nikāḥ. Artikel ini berargumen bahwa, menurut Al-Bangkalany, konsep kafā’ah sebagaimana dalam berbagai kitab fikih bukanlah patokan utama dalam memilih pasangan. Namun prinsip utama yang perlu ditegaskan adalah calon mempelai pria harus memiliki kemampuan dalam memenuhi kebutuhan rumah tangga setelah pernikahan dilangsungkan. Sedangkan tentang wali nikah, Al-Bangkalany berpendapat bahwa penyandang disabilitas (buta, tuli, dan bisu) dapat menjadi wali nikah dengan bantuan sarana pendukung. Wali nikah juga tidak ditentukan dari pengetahuan intelektual sang wali.]